2021
DOI: 10.3389/fnhum.2021.682011
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Frequency Oscillations on Scalp EEG in Infant Spasm: A Prospective Controlled Study

Abstract: ObjectiveWe quantitatively analyzed high-frequency oscillations (HFOs) using scalp electroencephalography (EEG) in patients with infantile spasms (IS).MethodsWe enrolled 60 children with IS hospitalized from January 2019 to August 2020. Sixty healthy age-matched children comprised the control group. Time–frequency analysis was used to quantify γ, ripple, and fast ripple (FR) oscillation energy changes.Resultsγ, ripple, and FR oscillations dominated in the temporal and frontal lobes. The average HFO energy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Some previous studies suggested the EEG features could be associated with the relapse of IS [ 7 10 , 20 ]. Hayashi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggested the EEG features could be associated with the relapse of IS [ 7 10 , 20 ]. Hayashi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp HFOs and FOs occurred more frequently in children with IS than in healthy controls ( 50 , 52 , 53 ) and more frequently during sleep than wakefulness in IS ( 52 ). The energy of gamma band events during sleep was also found to be higher in children with IS than healthy controls ( 51 ). Spatially, one study of IS reported that ripple rates were significantly higher than controls in the posterior parasagittal region and significantly lower in the frontal region ( 52 ), but a second study found the highest rates of gamma, ripple, and fast ripple events in the temporal and frontal lobes of children with IS ( 51 ).…”
Section: Computational Analysismentioning
confidence: 96%
“…Many studies have documented the occurrence of scalp HFOs and FOs during interictal periods, as well. These were most frequently studied using slow-wave sleep EEG, with detection of events in the gamma and ripple frequency bands ( 50 , 51 , 54 , 55 ), the ripple band ( 52 ), or the ripple and fast ripple bands ( 53 ). Scalp HFOs and FOs occurred more frequently in children with IS than in healthy controls ( 50 , 52 , 53 ) and more frequently during sleep than wakefulness in IS ( 52 ).…”
Section: Computational Analysismentioning
confidence: 99%
“…It is the largest single epilepsy subgroup affecting 13–45.5% of infants ( 2 ) with an annual incidence of 32.7/100 000 live births ( 3 ). In recent years, more and more studies have been conducted to discover that on scalp EEG, γ oscillations can better detect susceptibility to epilepsy than ripple and fast ripple oscillations in IS children ( 4 ). High-frequency oscillations (HFOs) and coupling between HFOs and slow-wave activity can trigger spasms ( 5 ).…”
Section: Introductionmentioning
confidence: 99%